Analysis Trends and Preferences Muslim tourists towards Halal Tourism Destinations - Magfiroh, Diana (Journal of Global Tourism, 2024)
This study analyzes the trends and preferences of Muslim tourists in selecting halal tourism destinations. Using a mixed-methods approach, which includes surveys and interviews with 400 Muslim tourists, the research reveals that key factors influencing destination choices include the availability of halal food (78%), prayer facilities (65%), family-friendly environments (55%), and cleanliness and safety (50%). The study also explores the role of technology, with 55% of respondents using halal tourism apps to plan their trips. The findings highlight challenges such as the lack of halal information (45%), insufficient halal certification at non-Muslim destinations (40%), and language barriers (30%). The results indicate that there is a growing demand for halal tourism infrastructure, and suggest strategies for improving halal certification, enhancing digital tools, and increasing transparency in destination offerings. This study provides valuable insights for tourism stakeholders in developing more inclusive and competitive halal tourism markets.